2016
DOI: 10.4236/ajps.2016.71017
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Determination and Antibacterial Activity of <i>Punica granatum</i> Peel Extracts against Plant Pathogenic Bacteria

Abstract: Plant pathogenic bacteria are recognized to be harmful microbes able to decrease the quantity and quality of crop production in the world. Punica granatum peel was screened for its potential use as biological control agent for plant pathogenic bacteria. P. granatum peel was successfully extract using n-hexane, methanol and ethyl acetate by maceration. The highest yield obtained by ethyl acetate showed that ethyl acetate extracted more compounds that readily soluble to methanol and n-hexane. For in-vitro antiba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The results were in a close agreement with that of Foss et al, (2014) and Barathikannan et al, (2016) who reported that hydroalcoholic and alcoholic extract of pomegranate fruit peels showed activity against the dermatophytes Trichophyton mentagrophytes, Trichophyton rubrum, Microsporum canis, and Microsporum gypseum. Mahajan et al, (2014); Khaleel et al, (2016); Mohammed et al, (2016); Akroum, (2017); Mostafa et al, (2017); Rosas-Burgos et al, (2017) The present study showed that hexane, ethyl acetate, and 80% ethanol extracts of fennel fruits did not affect the tested fungi. These results were in agreement with the study of Benlafya et al, (2015) and Thakur et al, (2013) who demonstrated that alcoholic extract of fennel seeds was ineffective against tested bacterial and fungal strains such as Escherichia coli, Bacillus subtilis, Salmonella abony, Candida albicans, and Aspergillus flavus.…”
Section: Determination Of the Active Components Of The Potent Extractssupporting
confidence: 45%
“…The results were in a close agreement with that of Foss et al, (2014) and Barathikannan et al, (2016) who reported that hydroalcoholic and alcoholic extract of pomegranate fruit peels showed activity against the dermatophytes Trichophyton mentagrophytes, Trichophyton rubrum, Microsporum canis, and Microsporum gypseum. Mahajan et al, (2014); Khaleel et al, (2016); Mohammed et al, (2016); Akroum, (2017); Mostafa et al, (2017); Rosas-Burgos et al, (2017) The present study showed that hexane, ethyl acetate, and 80% ethanol extracts of fennel fruits did not affect the tested fungi. These results were in agreement with the study of Benlafya et al, (2015) and Thakur et al, (2013) who demonstrated that alcoholic extract of fennel seeds was ineffective against tested bacterial and fungal strains such as Escherichia coli, Bacillus subtilis, Salmonella abony, Candida albicans, and Aspergillus flavus.…”
Section: Determination Of the Active Components Of The Potent Extractssupporting
confidence: 45%
“…However, none of these studies reported MIC values. The only study in which such information was available was the one by Khaleel et al [50], who tested the efficacy of the ethyl acetate extract of P. granatum peel against E. carotovorum and X. gardneri, finding MIC values of 3.125 and 6.25 mg•mL −1 , respectively. In comparison, the hydromethanolic extracts of P. granatum var.…”
Section: Comparison Of the Microbicidal Activity Of The Extractmentioning
confidence: 99%
“…The slope of the experimental tubes and that of the TC tube was seeded. The tubes were incubated at 37°C for 24 h. The MIC was the concentration of the first tube from which no microbial visible growth (Khaleel et al, 2016).…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%